ANALISIS CORPORATE IMAGE DAN KEPUASAN NASABAH BANK BRI KANTOR CABANG NATAR - Sri Suyarti (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
Banking world experiencing intense competition and always strive to maintaincustomers. Bank Rakyat Indonesia (BRI) Branch Natar South Lampung as bankingservices company that puts customer satisfaction trying to build a positive image thatconsumers would be interested in purchasing or re-use the services they provide. One wayto build a positive image in question is build customer satisfaction by setting the vision andmission of the company in the management of service oriented corporate image.Performance given the Bank BRI branch Natar overall have given satisfaction tothe customer in accordance with the expectations of the customers of Bank BRI BranchNatar.